2022
DOI: 10.3389/fvets.2022.1039519
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition of carapace, feces, and water column in captive juvenile green sea turtles with carapacial ulcers

Abstract: IntroductionGreen sea turtles are endangered marine reptiles. Carapacial ulcers will develop on juvenile green sea turtles during artificial rescue, seriously affecting their health and potentially leading to death.MethodsTo determine the pathogens causing ulcerative carapacial disease, we performed 16S and ITS high-throughput sequencing, and microbial diversity analysis on samples from carapacial ulcers, healthy carapaces, feces, and seawater of juvenile green sea turtles.ResultsOur analysis showed that chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…In this study, we couldn't attribute differences in the composition and structure of cloacal mycobiota to the turtles' age, sex, or hospitalization status, possibly due to the limited sample size per sampling site and condition assessed. Conversely, captive juvenile green turtles displayed more consistent mycobiota richness and diversity across various sampling sites and health conditions, unaffected by environmental fungi [30]. The taxonomic composition of cloacal and tank water fungal phyla in our study aligns with previously reported marine fungi groups found in green sea turtle faeces [30], as well as marine algicolous fungi, sediments, and sponges [48].…”
Section: Fungal Communities Of Loggerhead Cloaca Are Highly Heterogen...supporting
confidence: 87%
“…In this study, we couldn't attribute differences in the composition and structure of cloacal mycobiota to the turtles' age, sex, or hospitalization status, possibly due to the limited sample size per sampling site and condition assessed. Conversely, captive juvenile green turtles displayed more consistent mycobiota richness and diversity across various sampling sites and health conditions, unaffected by environmental fungi [30]. The taxonomic composition of cloacal and tank water fungal phyla in our study aligns with previously reported marine fungi groups found in green sea turtle faeces [30], as well as marine algicolous fungi, sediments, and sponges [48].…”
Section: Fungal Communities Of Loggerhead Cloaca Are Highly Heterogen...supporting
confidence: 87%
“…Conversely, captive juvenile green turtles displayed more consistent mycobiota richness and diversity across various sampling sites and health conditions, unaffected by environmental fungi [31]. The taxonomic composition of cloacal and tank water fungal phyla in our study aligns with previously reported marine fungi groups found in green sea turtle faeces [31], as well as marine algicolous fungi, sediments, and sponges [67]. Due to the lower resolution of the ITS2 gene marker and many unassigned fungal ASVs beyond the family level, this study offers just a general overview and serves as a foundation for further exploration of speci c groups of interest.…”
Section: Fungal Communities Of Loggerhead Cloaca Are Highly Heterogen...mentioning
confidence: 95%
“…during early development [18]. Recent work by Guo et al [31] provided initial insights into the fungal communities found on carapace (healthy and ulcerated), in faeces, and in the seawater of green turtle juveniles undergoing rehabilitation, however, comprehensive surveys of endobiotic fungal communities in loggerhead sea turtles have not yet been conducted. Given the ecological signi cance of loggerhead sea turtles in the Mediterranean basin ecosystem, their role as sentinels for pollution, and their potential to act as vectors for zoonotic diseases, a comprehensive approach including eukaryotic microorganisms is necessary to understand the loggerhead sea turtle microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Carapacial ulcers have been associated with Psychrobacter sp. and Coriobacteriaceae spp., which seem to act as opportunistic pathogens; in fact, they can be isolated also from healthy green sea turtles and seawater samples [ 139 ]. However, these bacteria pose a potential risk of human infection too; Psychrobacter spp.…”
Section: Other Bacterial Agentsmentioning
confidence: 99%
“…Cardiobacteriaceae agents were found in carapacial ulcers of sea turtles, although they seem to have a simple role as contaminant [ 139 ]. However, bacteria of this family, also found in healthy penguins, dolphins, and whales, may cause endocarditis and wound infections in humans [ 144 ].…”
Section: Other Bacterial Agentsmentioning
confidence: 99%